Thermal Simulation of Multiple Chips LED Module Using Computational Fluid Dynamic Software - Wong, Yau Yun (2016)
In recent years, high luminous efficiency light emitting diode (LED) with low power consumption has become the trend in lightning system. However, LED module produces large amount of heat and the heat produced greatly reduced the life span and the performance of LED module. This makes thermal management a critical issue to be solved. Recently, a lot of researches were carried out to improve the heat dissipation performance of the LED module and reduce the junction temperature of the LED chip. In this paper, the author modelled multiple-chip LED module using computational fluid dynamic software and analysed the thermal performance of the module. In the first part of the research, various model parameter such as materials of LED chip, substrate and thermal interface material (TIM) were studied so as to find out the optimized design in relate to the best thermal performance of LED module. In addition, the optimal thermal and optical properties of LED were investigated through various arrangements, namely number of LED chips, distance between the LED chips and the orientation of LED chips. In present study, a simple multiple-chip LED module was developed for the prediction of thermal performance by employing different designs of heat sink. Parametric studies of heat sink design were then discussed based on the simulation results. Lastly, an optimized four LED-chips module that produces high luminosity light output with junction temperature lower than 90 oC was designed and analysed.